The Crown: The Complete Final Season - Staunton, Imelda, 1956-; West, Dominic, 1969-; Debicki, Elizabeth; Pryce, Jonathan; Sony Pictures Home Entertainment (Firm) (Culver City, CA : Sony Pictures Home Entertainment, 2024)
A relationship blossoms between Princess Diana and Dodi Fayed before a fateful car journey has devastating consequences. Prince William tries to integrate back into life at Eton in the wake of his mother's death as the monarchy must ride the wave of public opinion. As she reaches her Golden Jubilee, the Queen reflects on the future of the monarchy with the marriage of Charles and Camilla and the beginnings of a new Royal fairytale in William and Kate.
Originally broadcast as single episodes of a television program in 2023.
Wide screen (2.00).
new dvd 2024 summer.
Imelda Staunton, Dominic West, Elizabeth Debicki, Jonathan Pryce, Lesley Manville, Olivia Williams.
Rating: Not Rated. CHV Rating: 14A
Closed captions (feature film only). Subtitles for the deaf and hard of hearing
Keywords: Elizabeth -- II, -- Queen of Great Britain, -- 1926-2022 -- Drama; Diana, -- Princess of Wales, -- 1961-1997 -- Drama; Charles -- III, -- King of Great Britain, -- 1948- -- Drama; Camilla, -- Queen, consort of Charles III, King of Great Britain, -- 1947- -- Drama; William, -- Prince of Wales, -- 1982- -- Drama; Catherine, -- Princess of Wales, -- 1982- -- Drama; Al Fayed, Mohamed, -- 1933-2023 -- Drama; Philip, -- Prince, consort of Elizabeth II, Queen of Great Britain, -- 1921-2021 -- Drama; Elizabeth, -- Queen, consort of George VI, King of Great Britain, -- 1900-2002 -- Drama; Margaret, -- Princess, Countess of Snowdon, -- 1930-2002 -- Drama; Women -- Political activity -- Great Britain -- Drama; Queens -- Great Britain -- Drama; Princesses -- Great Britain -- Drama; Prime ministers -- Great Britain -- Drama; Man-woman relationships -- Drama; Great Britain -- Politics and government -- Drama; Great Britain -- History -- Elizabeth II, 1952-2022 -- Drama; Television series; Video recordings for the hearing impaired; Historical television programs; Biographical television programs